The English Constitution - Bagehot, Walter (London Oxford University Press, 1952)
There is a great difficulty in the way of a writer who attempts to sketch a living Constitution-a Constitution that is in actual work and power. The difficulty is that the object is in constant change. An historical writer does not feel this difficulty: he deals only with the past; he can say definitely, the Constitution worked in such and such a manner in the year at which he begins, and in a manner in such and such respects different in the year at which he ends; he begins with a definite point of time and ends with one also. But a contemporary writer who tries to paint what is before him is puzzled and a perplexed: what he sees is changing daily. He must paint it as it stood at some one time, or else he will be putting side by side in his representations things which never were contemporaneous in reality.
With an introduction by "The First Earl Of Balfour."
Keywords: Great Britain -- Politics and government -- Constitutional history -- Constitutional law -- English Constitution (Bagehot, Walter) -- England -- Brougham and Vaux, Henry Brougham, Baron, 1778-1868 -- Peel, Robert, 1788-1850